2005
DOI: 10.1002/jor.20029
|View full text |Cite
|
Sign up to set email alerts
|

Composition and transport properties of human ankle and knee cartilage

Abstract: ABSTRACT:The incidence of osteoarthritis is significantly higher in the knee as compared to the ankle, suggesting that differences in the properties of cartilage from these joints may contribute to the development of osteoarthritis. As an avascular tissue, articular cartilage depends primarily upon diffusion for molecular transport. The goal of this study was to determine if differences in the structure and composition between ankle and knee cartilage were also reflected as differences in solute transport prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
2
38
1
Order By: Relevance
“…BASHIR et al reported that the intravenous administration of gadolinium compounds allowed the contrast agents to diffuse into patellar cartilage from both the articular surface and the subchondral bone (20). However, articular cartilage depends primarily upon diffusion for molecular transport (47), and articular cartilage on the femoral condyle is thinner than patellar cartilage (20,48). Thus, recent reports have shown that the direct administration of Gd-DTPA 22 has potential advantages for the MR imaging of cartilage (26,27,49).…”
Section: Discussionmentioning
confidence: 99%
“…BASHIR et al reported that the intravenous administration of gadolinium compounds allowed the contrast agents to diffuse into patellar cartilage from both the articular surface and the subchondral bone (20). However, articular cartilage depends primarily upon diffusion for molecular transport (47), and articular cartilage on the femoral condyle is thinner than patellar cartilage (20,48). Thus, recent reports have shown that the direct administration of Gd-DTPA 22 has potential advantages for the MR imaging of cartilage (26,27,49).…”
Section: Discussionmentioning
confidence: 99%
“…9B, D) are robust, but remain below native values (G*: 5-10 MPa at 0.01 Hz, collagen: 10-15%/ww); they are on par with engineered cartilage from previous studies. [52][53][54][55][56][57][58][59][60] On average by day 56, large constructs had reached sizes of Ø52 · 4.3 mm, weighed 8.1 g, had E Y of 450 kPa, and had 8.1%/ww GAG and 2.6%/ww collagen. The most robust Ø40 mm construct was cast with P0 cells and reached E Y = 623 kPa, 8.9%/ww GAG, and 3.5%/ww collagen.…”
Section: Discussionmentioning
confidence: 99%
“…For uncompressed cartilage tissue, we measure an average parallel diffusion coefficient, D k, within the middle zone of 3.8 mm 2 sec À1 . In a similar FRAP experiment, Fetter et al [31] reported a D k for the middle zone of 34 mm 2 sec À1 , which is 10 times higher. Earlier, Leddy and Guilak [27] measured an average perpendicular diffusion coefficient, D t , in the middle zone of around 55 mm 2 sec À1 .…”
Section: Comparison With Previous Diffusion Measurementsmentioning
confidence: 93%
“…Our experiments were performed on 30 mm thick microtomed sections taken from the cartilage middle zone. Fetter et al [31] studied full-thickness explants, and Leddy and Guilak [27] studied perpendicular diffusion in 2 mm thick sections. In all three experiments, the analysis of the fluorescence recovery assumes that diffusion occurs only in two-dimensions, i.e., parallel to the focal plane, ignoring any contribution to D k , from diffusion perpendicular to this plane (from D t ).…”
Section: Comparison With Previous Diffusion Measurementsmentioning
confidence: 98%